Ghost of Spruce Point - Tandon, Nancy (New York Aladdin, 2022)
Twelve-year-old Parker must unravel a curse to save his family's beloved Maine motel.
Twelve-year-old Parker has grown up in his family's Home Away Inn, nestled on a wooded peninsula in Maine called Spruce Point. His best friend, Frankie, has been staying at the inn every summer for years with her family. Together, they've had epic adventures based out of a nearby old treehouse that serves as their official headquarters for Kids Confidential Meetings. But lately, business at the inn hasn't been great, and Parker is pretty sure he knows why. It's long been rumored that Mrs. Gruvlig, one of the few year-rounders on Spruce Point, has unique abilities of the supernatural kind. And Frankie is absolutely sure she saw a ghost on Mrs. Gruvlig's property! As more and more spooky happenings occur around the Point, Parker and Frankie are convinced Spruce Point has been officially cursed.
Ages 8 to 12.
113622
Keywords: Blessing and cursing; Ghost stories; Hotels; Friendship; Paranormal fiction